Analisis Minat Siswa SMA Negeri 6 Kota Jambi terhadap Olahraga Renang - Honesti, Tamara; Murniati, Sri; Iqroni, David (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This research was motivated by the limited participation of students at SMA Negeri 6 Jambi City in swimming activities, despite the school's previous achievements in this sport. The study aims to determine students' level of interest in swimming and analyze the factors influencing it. A descriptive quantitative method with a survey approach was employed. Data collection was conducted through questionnaire distribution to 132 randomly selected students from a population of 882. The findings revealed that 52% of students fall into the moderate interest category, 41% high interest, 6% very high interest, and 2% low interest. Intrinsic factors such as attention, preference, and activity participation significantly contribute to interest levels, while extrinsic factors including peer influence, facilities, family support, and environmental conditions also play important roles. The research concludes that students' interest in swimming at SMA Negeri 6 Jambi City is reasonably good, though not yet optimal.